Improving Casuarina growth and symbiosis with Frankia under different soil and environmental conditions--review - Sayed, W F (Folia microbiologica, 2011)
Casuarinas are very important plants for their various uses and survival in adverse sites or harsh environments. As nitrogen fixation, in symbiosis with Frankia, is an important factor for the survival of these plants under various conditions, the basis for selecting both effective and tolerant Frankia strains and Casuarina spp., are provided. Enhancement of the symbiotic relationship between Frankia and Casuarina, by mycorrhizal infection and other biofertilizing microorganisms such as Bacillus and Azospirillum, is reflected by superior plant growth. Casuarina leaf litter is also a great source for both inorganic and organic nutrients. Therefore, careful management of the top soil layer under Casuarina trees is very important. Litter decomposition ratio is affected by many physical chemical and biological factors including temperature, moisture conditions, lignin, and C-to-N and N-to-P ratios in addition to soil biota. In general, here the above relations are discussed and an alleviation model is presented for important disturbances of natural and human origin made in soil and environment, especially in the dry regions. In conclusion, we suggest how to optimize the nitrogen fixation and plant growth under the prevalent conditions.
Keywords: Symbiosis; Soil Microbiology; půdní mikrobiologie; symbióza; Frankia; Magnoliopsida